Єврейська спільнота в умовах модерного світу: роздуми на шпальтах "Еврейского обозрения" (1884 р.) - Шара, Л. (Сiверянський літопис, 2023)
Мета статті – розкрити ключові теми єврейської публіцистики, оприлюдненої на сторінках
науково-літературного журналу «Еврейское обозрение» (1884 р.). Методи дослідження корелюються з означеною метою, є загальнонауковими (аналіз, синтез, індукція) та спеціально-історичними (історико-генетичний, історико-порівняльний). Наукова новизна розвідки зумовлена потребою
актуалізувати проблему «розмивання» традиційного світу єврейства в умовах модерного часу.
Висновки. Модерні перетворення другої половини ХІХ ст. суттєво позначилися на світосприй-
нятті й традиційному способі життєдіяльності єврейської спільноти. На шпальтах науково-популярного журналу «Еврейское обозрение» публіцистами були частково візуалізовані інноваційні моменти, якими «розмивалися» обшири традиційного світу єврейства. Аргументовано показано взаємообумовленість підвищення загального рівня грамотності єврейського населення, поширення
просвітництва та національного відродження, інтересу до власної історії й культури. Наголошено
на умотивованості появи літературно-історичного дискурсу про єврейство як націю, а не релігійну
конгрегацію «Мойсеєвого закону» та аргументовано безпідставність теорії про «шкідливість»
навчання у загальноосвітніх закладах.
Базовими чинниками проти акультурації єврейства публіцисти визнавали сталі традиції та іудаїзм. Задля поглиблення етнічної ідентичності пропонували просвітництво, популяризацію самобутності релігійно-обрядового життя єврейської громади, її історичної та літературної спадщини. The purpose of the article is to reveal the key themes of Jewish journalism published on the pages of
the scientific and literary journal «Yevreyskoe obozrenie». Research methods are correlated with the stated
goal, are general scientific (analysis, synthesis, induction) and special-historical (historical-genetic,
historical-comparative). The scientific novelty of intelligence is due to the need to actualize the problem of
«erosion» of the traditional world of Jewry in the conditions of modern times.
As a result of the research, we can make following conclusions. Modern transformations of the second
half of the 19th c. significantly affected the worldview and traditional way of life of the Jewish community.
In the columns of the popular scientific magazine «Yevreyskoe obozrenie» publicists partially visualized innovative
moments that «blurred» the expanses of the traditional world of Jewishness. The interdependence
of raising the general level of literacy of the Jewish population, the spread of enlightenment and national
revival, and interest in oneʼs own history and culture is shown in an argumentative manner. The motivation
for the appearance of the literary-historical discourse on Jewry as a nation, and not the religious congregation
of the «Mosesic Law», is emphasized, and the groundlessness of the theory about the «harmfulness»
of education in general educational institutions is pointed.
The publicists recognized stable traditions and Judaism as basic factors against the acculturation of
Jewishness. In order to deepen ethnic identity, they proposed enlightenment, popularization of the identity
of the religious and ritual life of the Jewish community, its historical and literary heritage.